Virtue and vice : religion, social hierarchy and gender in English murder and execution pamphlets, 1570-1620 - Walker, Patricia (Trinity College (Dublin, Ireland). Department of History, 2016)
This dissertation analyses how murder and execution pamphlets reflected and affirmed acceptable patterns of religious belief and social behaviour in late Elizabethan and Jacobean England. The key sources of this dissertation are 42 surviving pamphlets which describe 88 murders published between 1570 and 1620. I subject these texts to detailed analysis and track both similarities and differences regarding religious belief including temptation, repentance, providence and descriptions of God and the devil. Social concepts that are present within these texts include hierarchy, gender and acceptable levels of domestic violence. Authors constantly stressed the need for morality and repentance while also reminding readers about their social obligations to one another as well as their obligations to the reigning monarch. This dissertation also includes discussion and analysis of contemporary religious tracts alongside these murder and execution pamphlets including sermons, prayers, works of theology, conduct literature and marital literature of the period. This selection of contemporary authors encompasses a variety of religious and social backgrounds and demonstrates the pervasive and constant nature of the themes found in murder and execution pamphlets throughout the period in discussion. By comparing the language of cheap print with that of dogmatic, moralistic and popular literature, I investigate the influences and references that lay at the heart of popular pamphlets and demonstrate how this literature was part of the ongoing dialogue pertaining to morality, religion, gender and societal norms found in print during the late sixteenth- and early seventeenth- centuries. Chapter Two directly discusses representations of popular and official religious beliefs about God, the devil, sin, repentance and providential revelations of murders found in this cheap print. These pamphlets contained overt biblical references and passages and shared admonitions against sin with religious and moralistic publications. Pamphleteers engaged with Scripture and contemporary religious discussions and packaged these ideas in popular dialogues about murder and violence. The concepts of sin and providence are also analysed in Chapter Three in combination with a discussion of gender, specifically the character of the widow. Widows, as independent women, did not fit into England's patriarchal order. They existed on the peripheries of society and were sites of social anxiety. This chapter analyses representations of widows as scapegoats for violence, as murderers and as victims, while taking into account additional depictions of widows found in early modern drama and conduct literature. Dialogue about gendered behaviour continues in Chapter Four which addresses murders committed by male householders against their domestic subordinates: wives, children and servants. Male householders were supposed to behave in a specific manner or risk losing their masculine identities. They were expected to love their wives, properly raise their children and be kind masters to servants. These roles could only be accomplished through absolute control of one’s emotions and impulses at all times. Loss of control, however, meant a forfeiture of masculinity and the household could not function properly without a male head. Authors of this genre of cheap print appeared to be very much concerned with identifying who did or did not belong among the English Christian brethren. Chapter Five analyses the exclusionary language used by authors to identify three groups of sinful and dangerous outsiders: traitors, rogues and savages. By identifying who belonged among English Christian brethren, authors highlighted desirable characteristics of men and women in these pamphlets. Chapter Six also discusses concepts of belonging by highlighting the roles neighbours played in this literature and identifies the reciprocal expectations placed on them in late Elizabethan and Jacobean England. Neighbours created and regulated reputation within a community and also played a direct role in the apprehension of felons. Momentary lapses in neighbourly duties, on the other hand, allowed murderers to grow bold and cause havoc until order was once again restored by the reassertion of proper neighbourly bonds and duties. Chapter Seven focuses on descriptions of clothing of both victims and felons. In these pamphlets, clothing served as both weapons and disguises which granted murderers access to their victims or to escape. Clothing could be used to represent innocence in some pamphlets by being described in penitential terms. It could also represent guilt in others when people demonstrated a complete lack of respect for social hierarchy by dressing above their station. Representations of innocence and social contempt were also found in descriptions of clothing at the gallows where clothing allowed felons one final signal of dissent as they proceeded to their deaths.
Keywords: History, Ph.D.; Ph.D. Trinity College Dublin